High-latitude crochet: Solar-flare-induced magnetic disturbance independent from low-latitude crochet - Yamauchi, Masatoshi; Johnsen, Magnar Gullikstad; Enell, Carl-Fredrik; Tjulin, Anders; Willer, Anna; Sormakov, Dmitry A. (Annales Geophysicae, 2020)
A solar-flare-induced, high-latitude (peak at 70–75 ∘ geographic latitude – GGlat) ionospheric current system was studied. Right after the X9.3 flare on 6 September 2017, magnetic stations at 68–77 ∘ GGlat near local noon detected northward geomagnetic deviations (ΔB) for more than 3 h, with peak amplitudes of >200 nT without any accompanying substorm activities. From its location, this solar flare effect, or crochet, is different from previously studied ones, namely, the subsolar crochet (seen at lower latitudes), auroral crochet (pre-requires auroral electrojet in sunlight), or cusp crochet (seen only in the cusp). The new crochet is much more intense and longer in duration than the subsolar crochet. The long duration matches with the period of high solar X-ray flux (more than M3-class flare level). Unlike the cusp crochet, the interplanetary magnetic field (IMF) B Y is not the driver, with the B Y values of only 0–1 nT out of a 3 nT total field. The equivalent ionospheric current flows eastward in a limited latitude range but extended at least 8 h in local time (LT), forming a zonal current region equatorward of the polar cap on the geomagnetic closed region. EISCAT radar measurements, which were conducted over the same region as the most intense ΔB, show enhancements of electron density (and hence of ion-neutral density ratio) at these altitudes (∼100 km) at which strong background ion convection (>100 m s −1 ) pre-existed in the direction of tidal-driven diurnal solar quiet (Sq0) flow. Therefore, this new zonal current can be related to this Sq0-like convection and the electron density enhancement, for example, by descending the E-region height. However, we have not found why the new crochet is found in a limited latitudinal range, and therefore, the mechanism is still unclear compared to the subsolar crochet that is maintained by a transient redistribution of the electron density. The signature is sometimes seen in the auroral electrojet (AE = AU − AL) index. A quick survey for X-class flares during ...